Life Cycle Assessment of Organic Arabica Coffee Products - Elida Novita; Mukhamad Edrin Irfani (The University of Lampung, 2023)
Upstream to downstream activities of organic Arabica coffee in Klungkung Village can cause environmental pollution and have the potential to be a contributor to increased greenhouse gases (GHG) and inefficient use of energy. On the upstream side, Arabica coffee cultivation activities use organic fertilizers, but the type and dosage of organic fertilizers are without proper knowledge. On the downstream side, it uses various technologies and produces various wastes that are not yet environmentally friendly. This study aims to determine how much the impact of processing organic Arabica coffee products on the environment can be reduced so that the product can be said to be feasible as an environmentally friendly product. The method used is Life Cycle Assessment (LCA) which has stages, goals and scope, life cycle inventory, life cycle impact assessment, and interpretation. Processing organic Arabica coffee products produces a GWP of 18.0589 kg CO2-eq, and the energy use efficiency shows a NER value of 0.03 and a NEV of -33.12. The recommended alternative improvements are making all solid waste into organic fertilizer and anaerobic handling of liquid waste to produce biogas which can be used as an alternative fuel to replace LPG in the roasting process. If the alternative recommendations for improvement are implemented, it can reduce the GWP value to 6.3514 kg CO2-eq and increase the efficiency of energy use consisting of NER values of 4.53 and NEV of 126.46. Keywords: Arabica, GWP, Energy, LCA, Organic